Subspecies and Distribution. L.a.arcticusRoss,1819—BaffinI,BylotI,andMelvillePeninsula,NENunavut(NCanada). L.a.andersoniNelson,1934—C&NENorthwestTerritoriesandmostofNunavut(NWCanada). L.a.bangsiiRhoads,1896—NewfoundlandandNEL.a.(ECanada.) L.a.banksicolaManning&Macpherson,1958—BanksI,intheCanadianArcticArchipelago. L.a.groenlandicusRhoads,1896—W,N&NEice-freecoastalregionsofGreenland. L.a.hubbardiHandley,1952—PrincePatrickI,intheCanadianArcticArchipelago. L.a.labradoriusMiller,1899—SEBaffinI,NHudsonBayIs,coastalSNunavut,NEManitoba,NQuebec,andNWL.a.Peninsula(NCanada). L.a.monstrabilisNelson,1934—QueenElizabethIs,exceptPrincePatrickI,intheCanadianArcticArchipelago. L. a. porsildi Nelson, 1934 — S & SW ice-free coastal regions of Greenland. in Leporidae - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Subspecies and Distribution. L.a.arcticusRoss,1819—BaffinI,BylotI,andMelvillePeninsula,NENunavut(NCanada). L.a.andersoniNelson,1934—C&NENorthwestTerritoriesandmostofNunavut(NWCanada). L.a.bangsiiRhoads,1896—NewfoundlandandNEL.a.(ECanada.) L.a.banksicolaManning&Macpherson,1958—BanksI,intheCanadianArcticArchipelago. L.a.groenlandicusRhoads,1896—W,N&NEice-freecoastalregionsofGreenland. L.a.hubbardiHandley,1952—PrincePatrickI,intheCanadianArcticArchipelago. L.a.labradoriusMiller,1899—SEBaffinI,NHudsonBayIs,coastalSNunavut,NEManitoba,NQuebec,andNWL.a.Peninsula(NCanada). L.a.monstrabilisNelson,1934—QueenElizabethIs,exceptPrincePatrickI,intheCanadianArcticArchipelago. L. a. porsildi Nelson, 1934 — S & SW ice-free coastal regions of Greenland. Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Leporidae, pp. 107-148 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 144, DOI: 10.5281/zenodo.6625539